Experimental design and statistical analysis of protein buffer to purify hydrolases from the skim latex of hevea brasiliensis - Mohamed, Nazhirah; Yusof, Faridah (AENSI Publications, 2014)
A lipid acyl hydrolase (LAH) enzyme has been purified from skim latex serum, a waste product of Hevea brasiliensis, using DEAE Sepharose™ Fast Flow ion exchange chromatography. The ~45kDa active LAH was expressed by spectrophotometric study and SDS-PAGE. One-Factor-at-A-Time (OFAT) method and Central Composite Design (CCD) in Response Surface Methodology (RSM) were employed to optimize the protein buffer in order to improve purification. Design Expert® 6.0.8. software was applied using a 2-factor, 5-level to find the optimum pH and concentration of protein buffer to yield the highest lipase acyl hydrolase. In this study, it is concluded that purification at pH 8.0, 20 mM Tris-HCl buffer on ion exchange column chromatography results in the production of the highest total LAH activity (61.152 U). The study has good significance in that it is an initial attempt to purify LAH enzyme, which has known as antifungal agent, from skim latex.